Green Infrastructure in Jakarta, Basic Understanding and Implementation Efforts in Indonesian Cities - Oswar M Mungkasa (Applied Research on Civil Engineering and Environment (ARCEE), 2020)
Public awareness of the importance of conserving natural resources and ecosystems can accelerate the implementation of green infrastructure (GI) in Indonesia. One of the Indonesian government’s efforts to apply the principles of GI in urban areas in a structured and massive manner is through the Green City Development Program (P2KH) Ministry of Public Works and Public Housing (PUPR). The approach taken is Green Planning and Design, Green Open Space, Green Energy, Green Water, Green Waste, Green Building, Green Transportation, Green Community. The city that is the case study for discussion is Jakarta. Jakarta Smart City, Green Buildings, Urban Agriculture, and Child Friendly Integrated Public Space (RPTRA) are programs that successfully implemented. The implementation GI program easily accepted if based on the community.